Analisis Kontruktivisme terhadap Performa Guru dalam Pembelajaran Pendidikan Agama Islam (PAI) di Kelas X SMA Darul Hikmah - Munazzah Hurun Ainun; Asep Dudi Suhardini; Nurul Afrianti (UNISBA Press, 2022)
Abstract. In a learning process a teacher must give birth to various kinds of learning concepts, one of which is constructivism. Constructivism in a learning process where students actively build knowledge based on their cognitive structure, educators act as facilitators and providers of learning that focus on the success of active students and build concepts from their experiences. The purpose of this study was to determine whether there was a good influence in learning Islamic religious education (PAI) after applying the principles of constructivism. The method used is a qualitative method with a descriptive research type of case study. From this research, the teachers of class Xa IPA and Xb IPS are. Research data collection techniques using interviews, observation, and documentation. Data analysis includes steps of data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation. The results of data analysis showed that constructivism on teacher performance in Islamic religious education (PAI) learning in the class showed that constructivism analysis went well because according to the lesson plan implementation plan, the learning process was more varied so that students became active. The teacher's performance in the preparation of the lesson plans is in accordance with the principles of constructivism which has an effect on increasing student learning outcomes. Obstacles to implementing constructivism in Islamic religious education (PAI) learning are the difficulty of teachers in giving concrete and realistic examples in the learning process, teachers who do not want to change the learning model, schools are still limited in providing facilities such as media, projectors and so on. Abstrak. Dalam suatu proses pembelajaran seorang guru harus melahirkan berbagai macam konsep belajar salah satunya adalah kontruktivisme. Konstruktivisme dalam suatu proses belajar dimana siswa aktif membangun pengetahuan yang dilandasi oleh struktur kognitif yang dimilikinya, pendidik berperan sebagai fasilitator dan penyedia pembelajaran yang berfokus pada suksesnya siswa aktif dan membangun konsep-konsep pengalamanya. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat pengaruh baik dalam pembelajaran pendidikan agama Islam (PAI) setelah menerapkan prinsip konstruktivisme. Metode digunakan adalah metode kualitatif dengan jenis penelitian deskriptif tipe studi kasus. Dari penelitian ini adalah guru kelas Xa IPA dan Xb IPS. Teknik pengumpulan data penelitian menggunakan wawancara, observasi, dan dokumentasi. Analisis data meliputi langkah reduksi data, penyajian data, dan penarikan kesimpulan. Uji keabsahan data menggunakan triangulasi. Hasil analisis data menunjukan bahwa konstruktivisme terhadap performa guru dalam pembelajaran pendidikan agama Islam (PAI) di kelas tersebut menunjukkan analisis konstruktivisme berjalan dengan baik karena sesuai rencana pelaksanaan pembelajaran RPP membuat proses pembelajaran lebih bervariasi sehingga siswa menjadi aktif. Perfoma guru dalam penyusunan RPP diantaranya sesuai dengan prinsip konstruktivisme berpengaruh terhadap peningkatan hasil belajar siswa. Kendala menerapkan konstruktivisme dalam pembelajaran pendidikan agama Islam (PAI) guru kesulitan dalam memberi contoh yang konkrit dan realistik dalam proses pembelajaran, guru yang tidak ingin mengubah model pembelajaran, sekolah masih terbatas dalam menyediakan fasilitas seperti media, proyektor dan sebagainya.